Fragmentation, Space and Rentism in the Neoliberalization of Health: the case of Bogota - Valero-Julio, Edgar; Beuf, Alice; Rojas-Valencia, Hans; Tache-Victorino, Michael (Sociedad y Economía, 2020)
This paper aims to analyze the logic behind investment and the modalities of the reconfiguration of the Health area in Bogotá. The Neoliberal reforms of the 90’s, deepen through specific regulations in the 2000’s, has transformed a system that never acknowledged the universal attention as a civilian right. From interviews to different actors of the health system, bibliographic review, press and corporative reports, we can point how heterogeneous structures coexist, from ruined public hospitals, rentier entities that take over official resources, to advanced clinics that are projected towards to the conformation of clusters and health tourism. We show how the coexistence of different business models lead to a problematic distinction of scope of labor management and modalities of production of the city.